PROFESIONALISME GURU DALAM INTEGRASI TEKNOLOGI DIGITAL UNTUK PEMBELAJARAN MENDALAM DI SMA MUHAMMADIYAH SAMPIT - Putrining Aji, Galuh; Jumelan; Yayuk, Erna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology in 21st-century education demands a high level of teacher professionalism to create meaningful and deep learning experiences. However, in many schools, technology integration remains limited to basic device use and has not fully supported collaborative activities or the development of students’ critical thinking skills. This study aims to analyze teachers’ professionalism in integrating digital technology for deep learning, the types of technology utilized, and the supporting factors and challenges faced by teachers at SMA Muhammadiyah Sampit. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected through questionnaires administered to teachers (n = 10) and students (n = 50), while qualitative data were gathered through interviews and documentation. The results indicate that teachers possess a high level of professionalism in understanding digital tools and creating interactive teaching materials. Canva, YouTube, Quizizz, and Google Forms were the most frequently used platforms, mainly for presenting materials and conducting assessments. From the students’ perspective, the use of digital technology enhanced their understanding of the material and increased learning engagement. The main challenges identified were unstable internet connections and limited device availability. These findings highlight the need for further pedagogical training in digital to strengthen technology-based deep learning practices in schools.